Short-range quorum sensing controls horizontal gene transfer at micron scale in bacterial communities - Jordi van Gestel (Nature Portfolio, 2021)
Bacterial cells often communicate by the release and detection of small diffusible molecules, a process termed quorum-sensing. Here, the authors compare the communication range of quorum-sensing systems, and identify systems that enable cells to accurately detect micron-scale changes in community composition.